Crusticorallina gen. nov., a nongeniculate genus in the subfamily Corallinoideae (Corallinales, Rhodophyta). Issue 6 (15th September 2016) - Hind, Katharine R.; Gabrielson, Paul W.; P. Jensen, Cassandra; Martone, Patrick T.
Abstract : Molecular phylogenetic analyses of 18S rDNA (SSU) gene sequences confirm the placement of Crusticorallina gen. nov. in Corallinoideae, the first nongeniculate genus in an otherwise geniculate subfamily. Crusticorallina is distinguished from all other coralline genera by the following suite of morpho‐anatomical characters: (i) sunken, uniporate gametangial and bi/tetrasporangial conceptacles, (ii) cells linked by cell fusions, not secondary pit connections, (iii) an epithallus of 1 or 2 cell layers, (iv) a hypothallus that occupies 50% or more of the total thallus thickness, (v) elongate meristematic cells, and (vi) trichocytes absent. Four species are recognized based on rbc L, psb A and COI‐5P sequences, C. painei sp. nov., the generitype, C. adhaerens sp. nov., C. nootkana sp. nov. and C. muricata comb. nov., previously known as Pseudolithophyllum muricatum . Type material of Lithophyllum muricatum, basionym of C. muricata, in TRH comprises at least two taxa, and therefore we accept the previously designated lectotype specimen in UC that we sequenced to confirm its identity. Crusticorallina species are very difficult to distinguish using morpho‐anatomical and/or habitat characters, although at specific sites, some species may be distinguished by a combination of morpho‐anatomy, habitat and biogeography. The Northeast Pacific now boasts six coralline endemic genera, far more than any other region of the world.